Hunting and Gathering: Attempting to Assess Services to Distance Learning Students. Issue 3 (1st October 2016) - Hebert, Andrea
ABSTRACT: This case study presents the experiences of a newly hired distance learning librarian at a large academic library. Faced with taking over a position that lacked a dedicated staff member for two years, the librarian wanted to understand the current state of services. In the course of investigating and collecting data and while working through challenges, the librarian began to build her operations map and clarified her vision and values.